Timing of progesterone and allopregnanolone effects in a serial forced swim test. - Contreras, Carlos M.; Francisco Rodríguez-Landa, Juan; Bernal-Morales, Blandina; Gutiérrez-García, Ana G.; Saavedra, Margarita (Salud Mental, 2011)
The forced swim test (FST) is commonly employed to test the potency of drugs to reduce immobility as an indicator of anti-despair. Certainly, antidepressant drugs reduce the total time of immobility and enlarge the latency to the first immobility period. FST is preceded by the open field test (OFT) to discard any influence of changes in general motor activity that could interfere with immobility in the FST. Albeit progesterone and its α-reduced metabolite allopregnanolone produce antidepressant-like effects in the FST, the timing of actions is unknown. We hypothesized that the latency and duration of effects produced by progesterone and allopregnanolone may be characterized by repeated FST sessions; we therefore devised a serial-FST experimental design to evaluate the timing effects of these steroids on immobility, locomotion in the open field test, and grooming in the later as an indicator of response to stress. We included fifty-one ovariectomized adult Wistar rats weighing 200-250 g at the beginning of the experiments. They were ovariectomized by abdominal approach under anesthesia. Rats were housed six per cage, at room temperature (25 ± 1°C) under a 12 h/12 h light/dark cycle (lights ON at 7:00 a.m.) with ad libitum access to purified water and food. All of the experimental procedures followed National Institutes of Health Guidelines. The local Ethics Committee (Biomedical Research Institute, Universidad Nacional Autónoma de México) approved the experimental protocol. A first group received vehicle (2-hidroxypropyl-γ-cyclodextrin dissolved in injectable sterilized water to obtain a 35% solution, control group n=17), the second group progesterone (1.0 mg/kg, n=17), and the third group allopregnanolone (1.0 mg/kg, n=17). All single injections were applied by intraperitoneal route at a volume of 0.8 ml/kg. The effects of treatments were evaluated in the serial-FST at 0.25, 0.5, 1, 2, 4, 6, and 24 h after injection, in a rectangular pool (height, 60 cm; length, 30 cm; width, 50 cm), with 24 cm deep water (25 ±1°C). We evaluated the total time of immobility, during 5 min, considered as the principal indicator of an anti-despair effect. Before each session of serial-FST, locomotion was evaluated in the OFT during 5 minutes. The apparatus consisted on an acrylic box (height, 20 cm; length, 44 cm; width, 33 cm), with twelve squares delineated on the floor (11 × 11 cm). In the same OFT sessions, grooming was evaluated as an indicator of response to stress. Statistical analysis consisted in two-way analysis of variance (ANOVA) and Student- Newman-Keuls as post hoc test. Total time in immobility was the highest and remained at similar levels only in the control group throughout the seven sessions of the serial-FST. In the allopregnanolone group a reduction in immobility was observed beginning 0.5 h after injection and lasted approximately 1.5 h. Similarly, progesterone reduced immobility beginning 1.0 h after injection, and the reduction lasted for approximately 5.0 h. In all groups, locomotion in the OFT was reduced after the first serial- FST session and remained at similar low levels during the serial-FST. In the control group, grooming was reduced after the first serial-FST session and lasted 24 h, but grooming did not change in the progesterone-or allopregnanolone-treated rats. From a serial-FST design, we conclude that progesterone and allopregnanolone exert short time-dependent reductions in immobility and anti-stress-like effects no longer than 24 hrs, and seemingly a reduction in the response to stress, which may have some clinical applications.